Economic implications in inflammatory bowel disease: results from a retrospective analysis in an Italian Centre - Variola, Angela; Massella, Arianna; Geccherle, Andrea; Bocus, Paolo; Tessari, Roberto; Zuppini, Teresa; Ravasio, Roberto (Farmeconomia. Health economics and therapeutic pathways, 2017)
BACKGROUND: Inflammatory bowel disease (IBD) represents a group of chronic conditions characterized by elevated costs. Over the last years, also a considerable healthcare burden associated with IBD has emerged, due to an increasing use of biological drugs and hospitalization costs. Despite the creation of local or regional databases, data regarding healthcare expenditure are lacking in Italy. AIM: To evaluate the treatment cost (biological drugs and hospitalizations) for patients with ulcerative colitis (UC) or Crohn’s disease (CD) treated with biological drugs. METHODS: Disease severity was evaluated by clinical scores (partial Mayo score and Harvey Bradshaw Index). We analyzed retrospectively patients treated with biologics referred to our IBD Unit between May 2015-April 2016 who underwent at least six months of follow-up (last visit October 2016). We calculated a mean cost per month of treatment for each patient. We also investigated the presence of any correlation between the monthly cost of treatment and demographic or clinical variables. RESULTS: We enrolled 142 patients (52 UC, mean age 44.3 years, male 40.4%; 90 CD, mean age 38.8 years, male 56.7%). About half of CD patients (48.9%) underwent previous intestinal surgery. The disease severity was higher in UC group vs CD group. In UC group infliximab was the most prescribed biologic (51.9%), followed by golimumab (26.9%) and adalimumab (21.2%). While CD patients were treated with adalimumab in 54.4% and infliximab in 45.6%. The mean monthly cost of treatment was € 1,235.41 ± 358.38 for UC and € 1,148.92 ± 337.36 for CD (p = 0.16). In both groups expenditure due to biologics amounts for more than 80%. We found a correlation between costs and disease activity (UC: p < 0.01; CD: p < 0.01). CONCLUSION: The main cost is due to biological drugs, but patients enrolled were the most severe in comparison to the whole IBD population under conventional therapy. As no cost differences were found between biologic drugs and the way of administration (intravenous or subcutaneous), the therapeutic choice should be driven by clinical reasons and not only economic ones.